Implementing administrative evidence based practices: lessons from the field in six local health departments across the United States - Duggan, Kathleen (BMC Health Serv Res, 2015)
BACKGROUND: Administrative evidence based practices (A-EBPs) are agency level structures and activities positively associated with performance measures (e.g., achieving core public health functions, carrying out evidence-based interventions). The objectives of this study were to examine the contextual conditions and explore differences in local health department (LHD) characteristics that influence the implementation of A-EBPs. METHODS: Qualitative case studies were conducted based on data from 35 practitioners in six LHDs across the United States. The sample was chosen using an A-EBP score from our 2012 national survey and was linked to secondary data from the National Public Health Performance Standards Program. Three LHDs that scored high and three LHDs that scored low on both measures were selected as case study sites. The 37-question interview guide explored LHD use of an evidence based decision making process, including A-EBPs and evidence-based programs and policies. Each interview took 30–60 min. Standard qualitative methodology was used for data coding and analysis using NVivo software. RESULTS: As might be expected, high-capacity LHDs were more likely to have strong leadership, partnerships, financial flexibility, workforce development activities, and an organizational culture supportive of evidence based decision making and implementation of A-EBPs. They were also more likely to describe having strong or important relationships with universities and other educational resources, increasing their access to resources and allowing them to more easily share knowledge and expertise. CONCLUSIONS: Differences between high- and low-capacity LHDs in A-EBP domains highlight the importance of investments in these areas and the potential those investments have to contribute to overall efficiency and performance. Further research may identify avenues to enhance resources in these domains to create an organizational culture supportive of A-EBPs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-015-0891-3) contains supplementary material, which is available to authorized users.